Case law as a source of information - Zarębska, Honorata (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Case law research is a part of legal research, the process of identifying and retrieving information necessary to support legal decision-making. Nowadays it refers to work in an electronic environment and in use of specialized databases. They can be used by anyone with a need for legal information - lawyers, law librarians and common citizens. Case law research depends on country and its legal culture. There are apparent differences in retrieving information in civil law system and common law system. These differences relate to used information retrieval solutions and kind of collected information resources.